(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research :The aim of the research is to prepare rehabilitative exercises to reduce the severity of the deformation of the forward fall of the head, as well as to identify the effect of rehabilitative exercises in improving the flexibility and strength of the muscles working on the shoulders and back of the research sample, and to identify the effect of rehabilitative exercises to reduce the severity of the deformation of the forward fall of the head for the research sample. The researchers also intended to use the experimental method with the pre and post test for its suitability to the research problem. As for the research community, it reached (7) students who were chosen by the intentional method at the ages of (10-12) years, who had a deformity of the frontal fall of the head in (15 schools) from the Rusafa Education Schools. The third is the district of Abnaa Al-Rafidain in the province of Baghdad, and thus the research sample reached (71%) of the community of origin, and they were presented to a specialist doctor, conducting examinations, and taking x-rays for them by means of an X-Ray device. Hereditary, and the deformity was of a simple degree, and (2) of them were excluded, because the students’ families did not accept their participation, and thus the number of the sample reached (5) students. The duration of the qualifying program lasted three months, at the rate of three units per week, as the total number of the units of the qualifying program was (36) units. Tribal and remote The researchers concluded that the rehabilitative exercises worked to improve the subjects of the sample with the deformity of the forward fall of the head. Also, the variety of rehabilitative exercises had a significant impact on improving the tests of flexibility and muscular strength of the sample individuals with the deformity of the forward fall of the head.